Nrf2 as a Therapeutic Target in the Resistance to Targeted Therapies in Melanoma - Marie Angèle Cucci; Margherita Grattarola; Chiara Monge; Antonella Roetto; Giuseppina Barrera; Emilia Caputo; Chiara Dianzani; Stefania Pizzimenti (MDPI AG, 2023)
The use of specific inhibitors towards mutant BRAF (BRAFi) and MEK (MEKi) in BRAF-mutated patients has significantly improved progression-free and overall survival of metastatic melanoma patients. Nevertheless, half of the patients still develop resistance within the first year of therapy. Therefore, understanding the mechanisms of BRAFi/MEKi-acquired resistance has become a priority for researchers. Among others, oxidative stress-related mechanisms have emerged as a major force. The aim of this study was to evaluate the contribution of Nrf2, the master regulator of the cytoprotective and antioxidant response, in the BRAFi/MEKi acquired resistance of melanoma. Moreover, we investigated the mechanisms of its activity regulation and the possible cooperation with the oncogene YAP, which is also involved in chemoresistance. Taking advantage of established in vitro melanoma models resistant to BRAFi, MEKi, or dual resistance to BRAFi/MEKi, we demonstrated that Nrf2 was upregulated in melanoma cells resistant to targeted therapy at the post-translational level and that the deubiquitinase DUB3 participated in the control of the Nrf2 protein stability. Furthermore, we found that Nrf2 controlled the expression of YAP. Importantly, the inhibition of Nrf2, directly or through inhibition of DUB3, reverted the resistance to targeted therapies.